PERBAIKAN SUBSTANSI KURIKULUM MELALUI INOVASI DALAM MENGHADAPI PROBLEMATIKA ERA REVOLUSI 4.0 - Errin Tri Rahmawati; Erwin Apriliani; Fery Diantoro (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Abstract: Education is an effort to educate, guide, nurture, develop, and direct a person through the knowledge that is taught and practiced throughout life. In education there is something that guides us so that education can be carried out properly, namely the educational curriculum. Curriculum development is needed due to the various challenges and problems that arise in line with the changing times that are increasingly advanced. This cannot continue to be tolerated, so that various methods are used, one of which is by conducting educational innovations. The research method used in the production of this article is the method of collecting data through literature study techniques. The results of the discussion stated that educational innovation can be one of the instruments used in improving and perfecting an educational curriculum, even though there are many examples of innovations that fail in its implementation, but it will increasingly inspire a sense of presenting better innovations and models that are not always top-down but bottom-up. In conclusion, curriculum changes and improvements become important in line with the continuity of all possibilities that occur in relation to the development of society, science, technology and cultural arts at the local, national, regional and global levels in the future. Conceptual and contextual design of curriculum improvement must be carefully prepared. The completion of the PAI curriculum in accordance with the 21st century is expected that students can further develop their knowledge not only in theory but also can practise it in everyday life and make students Indonesian citizens who live in diversity, real tolerance and as an effort to instill a spirit of education. Characters with continuity arrangement between KD 1-KD 4. Keyword: challenge; curriculum; Islamic Education; Educational Innovation Abstrak: Pendidikan adalah usaha mendidik, membimbing, membina, menumbuh kembangkan, serta mengarahkan seseorang melalui ilmu-ilmu yang diajarkan dan dilakukan sepanjang hidup. Dalam pendidikan ada sesuatu yang menjadi pedoman kita agar pendidikan dapat dilaksanakan dengan baik, yaitu kurikulum pendidikan. Pengembangan kurikulum diperlukan akibat dari berbagai tantangan dan persoalan yang muncul sejalan dengan perubahan zaman yang semakin maju. Hal ini tidak dapat terus dibiarkan, sehingga berbagai cara dilakukan salah satunya mengadakan inovasi pendidikan. Metode penelitian yang digunakan dalam pembuatan artikel ini adalah metode pengumpulan data melalui teknik studi literatur. Hasil diskusi menyatakan bahwa inovasi pendidikan dapat menjadi salah satu alat instrument yang digunakan dalam memperbaiki dan menyempurnakan suatu kurikulum pendidikan, walaupun banyak contoh inovasi yang gagal dalam implementasinya, tetapi hal itu akan semakin menggugah rasa untuk menghadirkan inovasi-inovasi yang lebih baik dan modelnya yang tidak selalu top-down tetapi bottom-up. Kesimpulan, perubahan dan penyempurnaan kurikulum menjadi penting seiring dengan kontinuitas segala kemungkinan yang terjadi berkaitan dengan perkembangan masyarakat, ilmu pengetahuan, teknologi dan seni budaya pada tataran local, nasional, regional, dan global di masa depan. Rancangan konseptual dan kontekstual penyempurnaan kurikulum harus disiapkan secara matang. Dilakukannya penyempurnaan kurikulum PAI yang sesuai dengan abad 21 diharapkan bahwa siswa dapat lebih berkembang ilmunya tidak hanya bersifat teori tetapi juga dapat mempraktekkannya dalam kehidupan sehari-hari dan menjadikan siswa sebagai warga Indonesia yang hidup dalam keragaman, toleransi yang nyata dan sebagai suuatu upaya menanamkan jiwa pendidikan karakter dengam penataan kesinambungan antara KD 1-KD 4. Kata Kunci: Tantangan, Kurikulum, PAI, Inovasi Pendidikan